Proses Produksi Polymer Sebagai Proteksi Sistem Jaringan Distribusi Tegangan Menengah di PT. Powerindo Prima Perkasa - Marcel Ade Satria; Mustofa Abi Hamid (Pusat Riset dan Inovasi Nasional, 2025)
The medium voltage distribution network system is an integral part of the process of transmitting electrical energy from the substation to consumers. This transfer aims to supply electricity for daily use by consumers and can also be applied in industrial environments. The importance of electricity in modern development makes it a critical element; if a power outage occurs, our activities will be disrupted. Therefore, protection is needed within the medium voltage distribution network system to safeguard against damage to the network infrastructure, which could lead to power outages. To reduce the occurrence of such issues, protective components have been developed to protect the medium voltage distribution network facilities, ensuring the safety of consumers from the 24kV medium voltage distribution system, which could be fatal in case of direct contact.